On the foundations of computing - Primiero, Giuseppe (Oxford University Press, 2019)
This book is a technical, historical, and conceptual investigation into the three main methodological approaches to the computational sciences: mathematical, engineering, and experimental. Part I explores the background behind the formal understanding of computing, originating at the end of the nineteenth century, and it invesitagtes the formal origins and conceptual development of the notions of computation, algorithm, and program.Part II overviews the construction of physical devices to performautomated tasks and it considers associated technical and conceptual issues. It starts with the design and construction of the first generation of computingmachines, explores their evolution and progress in engineering (for both hardware and software), and investigates their theoretical and conceptual problems. Part III analyses the methods and principles of experimental sciences founded on computationalmethods. It studies the use ofmachines to performscientific tasks,with particular reference to computer models and simulations. Each part aims at defining a notion of computational validity according to the corresponding methodological approach.- Resumé vydavatele
Keywords: počítačová věda -- dějiny; počítače -- dějiny; computer science -- history; computers -- history; elektronické knihy; monografie; electronic books; monographs